Clustering of RNA co-expression network identifies novel long non-coding RNA biomarkers in squamous cell carcinoma - Nissinen, Liisa; Haalisto, Josefiina; Riihilä, Pilvi; Piipponen, Minna; Kähäri, Veli-Matti (Springer Nature, 2025)
Long non-coding RNAs (lncRNAs) have emerged as important players in cancer progression. Cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer with increasing incidence worldwide. The prognosis of the metastatic cSCC is poor, and currently there are no established biomarkers to predict metastasis risk or specific therapeutic targets for advanced or metastatic cSCC. To elucidate the role of lncRNAs in cSCC, RNA sequencing of patient derived cSCC cell lines and normal human epidermal keratinocytes was performed. The correlation analysis of differentially expressed lncRNAs and protein-coding genes revealed six distinct gene clusters with one of the upregulated clusters featuring genes associated with cell motility. Upregulation of the expression of lncRNAs linked to cSCC cell motility in cSCC and head and neck SCC (HNSCC) cells was confirmed using qRT-PCR. Elevated expression of HOTTIP and LINC00543 was also noted in SCC tumors in vivo and was associated with poorer prognosis in HNSCC and lung SCC cohorts within TCGA data, respectively. Altogether, these findings uncover a novel set of lncRNAs implicated in cSCC cell locomotion. These lncRNAs may serve as potential novel biomarkers and as putative therapeutic targets for locally advanced and metastatic cSCC.